Event-driven applications for hard-field tomography software modelling of forward and inverse solutions - Goh, C.L.; Abdul Rahim, Ruzairi; M. N., Abdullah; F. R., Hafiz; Tee, Z.C. (Penerbit UTHM, 2017)
This paper addresses mathematical modelling for a tomography application, in which forward and inverse problems are discussed in detail in terms of the projection modelling and image reconstruction algorithm. The forward modelling of the ultrasonic prototype is discussed to predict the sensor output for constructing cross-sectional images. Besides that, this paper also discusses the optimum image algorithm to solve the inverse problem for tomogram reconstruction. The applications are discussed with the supporting programming flow charts. Simulations were performed in foward and inverse applications respectively, and results were analysed using an image quality assessment technique called the Mean Structural Similarity Index, MSSIM. The results which indicated high MSSIM (>90%) in image analysis cocluded that the designed foward and inverse modelling applications can be deployed in real-time systems.